Community Livelihood Diversification as a Result of Mining Industry Activities: A Case Study of Soligi Village, South Halmahera - Izzudin, Muhammad; Santoso, Anang Dwi; Baiquni, Muhammad; Nugroho, Agung Satriyo (Jurnal Ilmu Sosial dan Humaniora, 2022)
Indonesia is one of the world's largest archipelagic countries. Diversification is the process of increasing household economic income in various sectors to improve welfare and survival opportunities. This study demonstrates that the people of Obi Island's livelihoods are diversifying due to mining and pressure from the immigrant population. This study is necessary to determine how mining depletes natural resources affects the livelihood strategies of the Indonesian archipelagic community, particularly in Maluku. On the other hand, they must contend with dwindling natural resources. This study employed a semi-structured questionnaire to conduct a home survey with 153 respondents in Soligi Village. In-depth interviews were also conducted to delve deeper into the research findings. This study demonstrates that physical capital and natural capital are the essential livelihood assets for the inhabitants of Soligi Village, and mining has resulted in the diversification of people's occupations into non-permanent mining employees.Â